Analisis Vegetasi Gulma Pada Tanaman Buah Naga Merah (Hylocereus polyrhizus, L.) di Kecamatan Batang Anai, Kabupaten Padang Pariaman, Sumatera Barat - Elsa Olivia Perdana; Zuhri Syam (Jurnal Biologi Universitas Andalas, 2013)
Analysis of weed vegetation on red dragon fruit plants Hylocereus polyrhizus, L.on sandy soils and not gritty in the District Batang Anai, Padang Pariaman has conducted from March-April 2013 by using the of random squares method with the number 12 plot size1x1 m at each location. The results showed on sandy soils have been found 11 families, 20 genera, 21 species, and 822 individuals. Amaranthus lividus SDR has the highest value (25.80%), and the lowest value of SDR Galinsoga parviflora (0.90%), is the diversity index H'= 2.16 (moderate). While the sandy soil found in 6 families, 12 genera, 15 species and 1070 individuals. Eleusine indica the highest value of SDR (14.1%), and the lowest value of SDR Ageratum conyzoides, diversity index H'= 2.25 (moderate). Index of similarity of 38.88% (significantly different). Keywords: Weeds, Hylocereus polyrhizus. L, composition, structure